Effect of genetic polymorphism on individualized treatment of tacrolimus in patients with primary nephrotic syndrome - Xiong Lian-lian; Yi Bin (Linchuang shenzangbing zazhi)
As a highly effective immunosuppressant, tacrolimus（TAC,FK506）has been widely applied for primary nephrotic syndrome.However, excessive dose or underexposure of TAC remains rampant in clinical practices.Recent studies have indicated that cytochrome P450 family 3 subfamily A4（CYP3 A4）,cytochrome P450 family 3 subfamily A5（CYP3 A5）metabolic enzymes and ABC transporter play important roles in its metabolisms and transports and single nucleotide gene polymorphisms may partially explain differences in pharmacokinetic profiles among individuals.This review summarized the effects of CYP3 A4/3 A5 and ABC transporter gene polymorphisms on TAC plasma concentrations in patients with primary nephrotic syndrome.It was intended as a theoretical basis for individualized treatment of TAC in this population.